Fibrillary Glomerulonephritis Diagnosis Is Enhanced by DNAJB9: Three Cases with Different Clinical, Anatomopathologic Features and Outcomes - José C. De La Flor; Marco Dominguez Davalos; Tania Linares Grávalos; Marina Alonso-Riaño; Francisco Díaz; Celia Rodríguez Tudero; Rocío Zamora González-Mariño; Michael Cieza Terrones; Jesús Hernández Vaquero (Pathophysiology)
Background: Fibrillary glomerulonephritis (FGN) is a rare and poorly understood kidney disease characterized by the deposition of non-amyloid fibrils in the glomeruli. Its clinical heterogeneity and high rate of progression to end-stage renal disease (ESRD) pose significant diagnostic and therapeutic challenges. This case series aims to enhance awareness of FGN and emphasizes the need for further research to improve patient outcomes. Case Reports: We reviewed the clinical, histopathological, and therapeutic data of three patients with FGN diagnosed by kidney biopsy. The cases included variations in clinical presentation from nephrotic syndrome to rapidly progressive glomerulonephritis (RPGN). Diagnostic methods incorporated light microscopy, immunofluorescence, and electron microscopy, with the integration of DnaJ homolog subfamily B member 9 (DNAJB9) staining for confirmation. Patient 1 showed a more favorable response to rituximab, achieving complete remission (CR) at 6 months and maintaining CR after 3 years. Patient 2 showed only partial remission after 2 years following treatment with rituximab. Patient 3 presented with RPGN and rapidly progressed to ESRD despite aggressive immunosuppressive therapy. Discussion: DNAJB9 has emerged as both a specific and sensitive biomarker in patients with FGN and has facilitated accurate differentiation from other glomerulopathies. This series underscores the variability in clinical outcomes and responses to therapy as well as the importance of early and accurate diagnosis. Conclusions: FGN remains a diagnostic and therapeutic challenge due to its rarity and heterogeneity. Advances in biomarkers like DNAJB9 have improved diagnostic accuracy, distinguishing FGN from similar conditions such as immunotactoid glomerulopathy. Further research into pathophysiological mechanisms and targeted therapies is essential to optimize management and outcomes for affected patients.